(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
History teachers work on techniques and methods to inspire learners. If the teacher gets the recipe right in the classroom, history learners will enjoy and apply themselves to the subject, their understanding of content will increase, and they will acquire the necessary skills to achieve results. A technique used to inspire learners beyond the confines of the covers of a textbook, will be shared. The technique includes inviting outside speakers to share their curriculum-relevant personal stories and experiences with learners in the classroom. It will be argued that the value of introducing other ‘voices’ into the history classroom to enrich teaching and learning is only effective if underpinned by an ethos which advocates active citizenship, reinforced by a passionate teacher with subject specific knowledge, in a classroom structured to facilitate critical conversation.